2019
DOI: 10.1186/s41043-019-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Milk handling practices and consumption behavior among Borana pastoralists in southern Ethiopia

Abstract: BackgroundSafety and wholesomeness of milk intended for human consumption are influenced by various interlinked factors. However, information on what these factors are, especially in the pastoral traditional communities of Ethiopia, is largely lacking. The objective of this study is to assess the hygienic milk production, processing and consumption practices, and behaviors of Borana pastoralists.MethodsThe study used qualitative participatory research methods. Individual semi-structured interviews, focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 44 publications
2
83
0
Order By: Relevance
“…While motorcycles remain the major means of transportation of milk in Nakasongola, the milk was further exposed to long hours of high tropical heat. Subsequently, poor quality and similar observations have been reported in Zimbabwe and elsewhere (Amenu et al 2019;Paraffin et al 2018;Ayele et al 2017).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While motorcycles remain the major means of transportation of milk in Nakasongola, the milk was further exposed to long hours of high tropical heat. Subsequently, poor quality and similar observations have been reported in Zimbabwe and elsewhere (Amenu et al 2019;Paraffin et al 2018;Ayele et al 2017).…”
Section: Discussionsupporting
confidence: 70%
“…The consumption of raw milk is attractive to consumers with cultural beliefs and preferences for raw milk, particularly among the pastoralists in Uganda (Tumwine et al 2015) and elsewhere in sub-Saharan Africa (Caudell et al 2019;Ayele et al 2017). Traditionally, raw milk is perceived to have health benefits (Amenu et al 2019) and unique flavours, but these assertions lack scientific evidence. On the contrary, drinking raw milk is associated with transmission of diseases to consumers (Tumwine et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The situation in sub-Saharan Africa appears to be much worse, but it remains to be proven whether, due to frequent and higher levels of exposure, people are already "naturally vaccinated" because otherwise one would think even more losses of lives must be occurring. There is also resistance to recommendations to avoid unpasteurized dairy products and misconception about the health benefits of raw milk [13,14]. Meanwhile, the infections (and the probable ensuing diseases) continue to spread, which can be even more disabling when antibiotic resistance is added to the equation.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that people buy raw milk and consume it on the spot during market days and, sometimes, children consume goat milk directly from the udder ( Figure 1 ). Other practices observed that could potentially impair the health of consumers include selling raw milk for direct consumption on market days without heat treatment [ 42 ].…”
Section: Public Health Significance Of Goat Tuberculosismentioning
confidence: 99%
“…Milk consumption directly from the udder of a goat by children in Borana (a common practice during herding; source: [ 42 ]).…”
Section: Public Health Significance Of Goat Tuberculosismentioning
confidence: 99%